Identification of Thymocyte Subset by Multicolor Flow Cytometry ED LSR II FACSDriva - FlowJo Software Analysis - H. Harapan; W. Wienands; I. Ichsan; Ana Indrayati (Indonesian Journal of Biotechnology, 2008)
In their development, thymocytes express different cell surface molecules that important for identification of thymocyte subset. It’s not easy to detect this cell surface molecules to determine the thymocyte subpopulation for research. Here we used multicolor flow cytometry ED LSR II FACSDriva - FlowJo software to identify of thymocyte subset from thymocyte sample solution using several antibodies such as mouse anti rat CD2-FITC, mouse anti rat CD45RC-PE, mouse anti rat CD4-APC, mouse anti rat CD8á-PerCP, mouse anti rat CD3-Biotin + PE-Cy7 or APC-Cy7. We determined double negative and single positive thymocyt subset (CD4 or CD8), found that the double negative thymocyte subset express CD2 and CD45RC. It was useful to determine the thymocyte subset using multicolor flow sitometry ED LSR II FACSDriva - FlowJo software.